2019
DOI: 10.15196/rs090103
|View full text |Cite
|
Sign up to set email alerts
|

A literature review and categorisation of sustainability-aimed urban metabolism indicators: a context, indicator, mechanism, outcome analysis

Abstract: Keywords:urban metabolism, urban metabolism indicator, sustainability, CIMO approach Urban metabolism has been advanced as an approach to quantifying energy and resource use and supply in the modern urban system. It is a multidisciplinary approach focused on providing insight into the behaviour of cities for drafting effective proposals for a more humane and ecologically responsible future. Urban metabolism indicators could play an important role in promoting the science and practice of urban metabolism for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Ez a klímaszkeptikusnak is nevezhető meggyőződés, valamint az annak megfelelő attitűd, miszerint a klímaváltozás hatásai miatt nincs különösebb ok az aggodalomra, empirikus eredmények szerint úgy tűnik, nagyobb valószínűséggel jellemző az idősebb korosztályokra és az alacsonyabb iskolai végzettségűekre. De területi különbségeket is feltártak ugyanezek az elemzések (Weber-Stern 2011;Whitmarsh 2011;Franzen-Vogl 2013;Milfont et al 2015;Shi et al 2016;Poortinga et al 2019;Song-van Timmeren-Wandl 2019;Bodor-Grünhut 2021). Utóbbi aspektus sokáig nem volt homlokterében a vizsgálatoknak (Freudenburg-Mcginn 1987), ma azonban már az adott térhez való kötödés, területi identitás (pl.…”
Section: Szakirodalmi/elméleti áTtekintésunclassified
“…Ez a klímaszkeptikusnak is nevezhető meggyőződés, valamint az annak megfelelő attitűd, miszerint a klímaváltozás hatásai miatt nincs különösebb ok az aggodalomra, empirikus eredmények szerint úgy tűnik, nagyobb valószínűséggel jellemző az idősebb korosztályokra és az alacsonyabb iskolai végzettségűekre. De területi különbségeket is feltártak ugyanezek az elemzések (Weber-Stern 2011;Whitmarsh 2011;Franzen-Vogl 2013;Milfont et al 2015;Shi et al 2016;Poortinga et al 2019;Song-van Timmeren-Wandl 2019;Bodor-Grünhut 2021). Utóbbi aspektus sokáig nem volt homlokterében a vizsgálatoknak (Freudenburg-Mcginn 1987), ma azonban már az adott térhez való kötödés, területi identitás (pl.…”
Section: Szakirodalmi/elméleti áTtekintésunclassified
“…Techniques under this umbrella include accounting methods such as material and energy flow analysis, and modelling methods, such as life cycle assessment (LCA) (Bjorn et al, 2020), and input/output analysis, which have also been combined in various ways to form hybrid approaches (Cui, 2018;Morris et al, 2020;Song et al, 2019;Zhang et al, 2015).…”
Section: Urban Metabolism Approachesmentioning
confidence: 99%
“…Recent reviews of urban metabolism approaches have identified methods frequently used (Beloin-Saint-Pierre et al, 2017;Shmelev and Shmeleva, 2019;Song et al, 2019) and indicators targeted (Cui, 2018;Shmelev and Shmeleva, 2019;Song et al, 2019) or focused on particular tools such as LCA (Mirabella et al, 2019), however have not analysed these against planetary boundaries explicitly, and generally do not consider social outcomes at all (Céspedes Restrepo and Morales-Pinzón, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%